Sistem Akuntansi Penyaluran Kredit Oleh Lembaga Perkreditan Desa (LPD) Adat Pakraman Bebetin Kepada Pedagang Pasar Desa Bebetin - Komang Wahyu Wedani (ARTHA SATYA DHARMA, 2025)
LPD is a bank in Pakraman Village and is involved in making village development a success, especially in the village economic sector. The study entitled "Accounting System for Credit Distribution by the Bebetin Pakraman Customary Village Credit Institution (LPD) to Bebetin Village Market Traders" raises the following questions: How does Bebetin Village implement LPD credit allocation, and what are the efforts of the LPD in Bebetin Village to support the community's economy? The research carried out aims to find out the mechanism used by the Bebetin Traditional Village LPD in considering loans to prospective debtors. This research uses observational research methods, interviews and documentation. Based on the investigation carried out, it was found that the Bebetin LPD had not fully implemented the loan disbursement procedures that apply in the Bebetin Traditional